Use of the Mental Health Gap Action Programme (mhGAP) by mental health volunteers in the UK: examples from South Asian diaspora charities - Leya Luhar; Aditi Arya; Raeesah Rafiq; Nandini Chakraborty (BJPsych Bulletin)
The Mental Health Gap Action Programme (mhGAP) was launched by the World Health Organization (WHO) in 2008 to scale up services for mental, neurological and substance use disorders for low- and lower-middle-income countries. Subsequently, an updated mhGAP intervention Guide (mhGAP-IG 2.0) was released in 2016. This study explores the use and effectiveness of mhGAP-IG 2.0 by mental health volunteers of two South Asian charities in the UK. Semi-structured interviews were carried out with eight volunteers. The core themes identified were mental health awareness, mental health education, empathy and care, social perception and bias within the South Asian community, and personal development. The study identified mhGAP as a tool with transformative potential. Although the WHO originally planned the mgGAP-IG as a tool for low- and middle-income countries with limited mental health resources, this study demonstrates its usefulness even in high-income countries, as a foundation to educate volunteers working in mental health.